Hypolipidemic effect of thymoquinone in heat stressed male rats - Al-Sa’aidi, Jabbar A. A.; Ali, Zainab S. (Al-Qadisiyah Journal of Pure Science, 2017)
The present study has been conducted to investigate the hypolipidemic effect of thymoquinone in heat stressed adult male rats. Seventy two adult male Wistar rats (aged: 80 days, weighted: 162±5.6 g) have been divided into 4 experimental groups (18 animals each), and daily administered for 6 weeks with; drinking water (p.o) under normal ambient temperature (control group); drinking water (p.o) and daily exposed to high ambient temperature (35-40 ºC) for 6 hours (HS group), thymoquinone (50 mg/kg BW, po) and daily exposed to high ambient temperature (35-40 ºC) for 6 hours (HSTQ group), and thymoquinone (50 mg/kg BW, po) under normal ambient temperature (TQ group). At 2, 4, and 6 weeks, six males from each group have been anaesthetized by intraperitoneal injection of 0.3 ml of ketamin and 0.1 ml of xylazin /200 g bw, sacrificed, and blood samples were obtained from abdominal vein for assessment of serum lipid profile (total cholesterol; T-c, triglycerides; TG, high density lipoprotein; HDL-c, low density lipoprotein; LDL-c, and very low density lipoprotein; VLDL-c). During all of the experimental periods, significant increase of T-c, LDL-c, and VLDL-c concentrations have been recorded in HS group compared with control and TQ groups, whereas that of HSTQ group were significantly declined compared with HS group, but still they were significantly higher than that of control and TQ groups. TG and HDL concentration showed significant increase at the same periods. It can be concluded that 50 mg/kg b.w. of TQ suspention drenching for 2, 4, and 6 weeks perform positive role in ameliorating the different complications of oxidative stress produced by heat stress by induction of hypolipidemic effect.